Analyzing the Thinking Trajectory of Students with Dyscalculia in Solving Spatial Mathematical Problems - Anisa Raihan Fadilla; Kamid Kamid; Rohati Rohati (Journal of General Education and Humanities, 2025)
This study employs a qualitative descriptive case study design to explore the thinking trajectories of two seventh-grade junior high school students who exhibit symptoms of dyscalculia when solving mathematical spatial problems. Dyscalculia is a specific learning difficulty that affects a student’s ability to understand and manipulate numerical and spatial information. The research aims to analyze how these students process mathematical problems, particularly focusing on the second phase of Simon's learning trajectory theory: the thinking trajectory. The study assessed five cognitive stages: connection, representation, communication, reasoning, and problem-solving. The research was conducted at SLB Prof. Dr. Sri Soedewi Masjchun in Jambi, Indonesia, from January to February 2025. Data collection techniques included written tests and in-depth interviews. Findings indicate that students with dyscalculia demonstrated confusion and limitations in all five cognitive processes assessed. The students often showed non-linear thinking patterns, with disruptions evident at the connection and representation stages due to limited conceptual understanding and low visual-spatial ability. For instance, one student relied heavily on external help to recall shapes and formulate strategies. At the same time, another tended to use trial-and-error approaches, struggled to provide logical explanations, and demonstrated confusion when translating verbal information into visual form. The implications suggest that additional support and inclusive instructional strategies, such as using concrete visual aids or 3D models, are essential. Teachers should adapt their methods to accommodate students with dyscalculia, helping them improve spatial reasoning and mathematical comprehension.